Le droit de recours de l'entrepreneur contre l'ingénieur ou l'architecte à la lumière d'arrêts récents de la Cour suprême - Rousseau-Houle, Thérèse (Les Cahiers de droit)

(untitled) (Faculté de droit de l’Université Laval, 1979)
This paper surveys recent Supreme Court decisions dealing with the relationship between building contractors and architects or engineers participating in the same project. Normally, the agreement between the owner and the architect or the owner and the engineer vests no rights in the building contractor. The latter may only sue the architect or the engineer on an extra-contractual basis. Proceedings may then take the form of a recursory action, where the contractor, having been held jointly and severally liable towards the owner, attempts to have the architect or engineer take their share of liability. Alternatively, proceedings could be taken on the basis of a delict, in cases where negligence is alleged by the contractor against the architect or engineer. The Supreme Court seems inclined to view the problem from a contract perspective, and to restrict opportunities to sue on the basis of a delict.